Cognitive Deficits in Brain Tumor Survivors - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
The results of studies of cognitive deficits in long-term survivors of childhood brain tumors are summarized from 31 published reports between 1968-1989 in a review paper from the Division of Child Neurology, The Children's Hospital, Philadelphia and the Department of Neurology, Children's National Medical Center, George Washington University, Washington, DC.